Intensity Modulation: A Novel Approach to Percept Control in Spinal Cord Stimulation. Issue 3 (19th October 2015) - Tan, Daniel; Tyler, Dustin; Sweet, Jennifer; Miller, Jonathan
Abstract : Objective: Spinal cord stimulation (SCS) can be effective for neuropathic pain, but clinical benefit is sometimes inadequate or is offset by stimulation‐induced side‐effects, and response can be inconsistent among patients. Intensity‐modulated stimulation (IMS) is an alternative to tonic stimulation (TS) that involves continuous variation of stimulation intensity in a sinusoidal pattern between two different values, sequentially activating distinct axonal populations to produce an effect that resembles natural physiological signals. The purpose of this study is to evaluate the effect of IMS on the clinical effect of SCS. Methods: Seven patients undergoing a percutaneous SCS trial for postlaminectomy syndrome were enrolled. Thresholds for perception, pain relief, and discomfort were measured and used to create patient‐specific models of axonal activation and charge delivery for both TS and IMS. All participants underwent three two‐min periods of blinded stimulation using TS, IMS, and placebo, and were asked to describe the effect on quality of the sensory percept and pain relief. Results: All participants perceived IMS differently from placebo, and five noted significant differences from TS that resulted in a more comfortable sensation. TS was described as electric and tingling, whereas IMS was described as producing a focal area of deep pressure with a sense of motion away from that focus. The anatomic location of coverage was similar between the two forms of stimulation, although one participant reported better lower back coverage with IMS. Computer modeling revealed that, compared with TS, IMS involved 36.4% less charge delivery and produced 78.7% less suprathreshold axonal activation. Conclusions: IMS for SCS is feasible, produces a more comfortable percept than conventional TS, and appears to provide a similar degree of pain relief with significantly lower energy requirements. Further studies are necessary to determine whether this represents an effective alternative to tonic SCS for treatment of neuropathic pain.